2016
DOI: 10.1093/toxsci/kfw094
|View full text |Cite
|
Sign up to set email alerts
|

Editor's Highlight: Identification and Characterization of Teratogenic Chemicals Using Embryonic Stem Cells Isolated From a Wnt/β-Catenin-Reporter Transgenic Mouse Line

Abstract: Embryonic stem cells (ESCs) are commonly used for the analysis of gene function in embryonic development and provide valuable models for human diseases. In recent years, ESCs have also become an attractive tool for toxicological testing, in particular for the identification of teratogenic compounds. We have recently described a Bmp-reporter ESC line as a new tool to identify teratogenic compounds and to characterize the molecular mechanisms mediating embryonic toxicity. Here we describe the use of a Wnt/β-Cate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Our data on thalidomide support this notion and indicated that our luminescence-based assay may have a high sensitivity and improved assay performance. Other reporter cell lines for developmental toxicity testing based on a fluorescence readout or β-galactosidase staining did not show increased sensitivity compared to the conventional readout of beating cardiomyocytes (Kugler et al 2015 , 2016 ). Furthermore, luminescence assays are less susceptible to autofluorescent chemicals than fluorescence-based assays (Fan and Wood 2007 ).…”
Section: Discussionmentioning
confidence: 98%
“…Our data on thalidomide support this notion and indicated that our luminescence-based assay may have a high sensitivity and improved assay performance. Other reporter cell lines for developmental toxicity testing based on a fluorescence readout or β-galactosidase staining did not show increased sensitivity compared to the conventional readout of beating cardiomyocytes (Kugler et al 2015 , 2016 ). Furthermore, luminescence assays are less susceptible to autofluorescent chemicals than fluorescence-based assays (Fan and Wood 2007 ).…”
Section: Discussionmentioning
confidence: 98%
“…Another strategy used to generate transgenic ES cell lines is to isolate ESCs from transgenic mouse models, which has led to the generation of two reporter mESC lines that can be used to monitor Wnt and TGF-βb signaling ( Kugler et al, 2017 , Kugler et al, 2016 ). Both models have been tested with a small set of developmental toxicants (valproic acid, retinoic acid, and 6-aminonicotinamide), and reporter activity correlates well with subsequent cardiomyocyte differentiation assays, demonstrating the validity of these approaches for the small set of chemicals tested.…”
Section: Stem Cell Biology and Its Application In Dart Testingmentioning
confidence: 99%
“…Another strategy used to generate transgenic ESC lines is to isolate ESCs from transgenic mouse models, which has led to the generation of 2 transgenic mESC lines that can be used to monitor Wnt and TGF-b signaling (Kugler et al, 2015(Kugler et al, , 2016. Both models have been tested with a small set of developmental toxicants (valproic acid, retinoic acid, and 6-aminonicotinamide), and reporter activity correlates well with subsequent cardiomyocyte differentiation assays, demonstrating the validity of these approaches.…”
Section: Transgenic Reporter Strainsmentioning
confidence: 99%